2013
DOI: 10.1080/13657305.2013.812157
|View full text |Cite
|
Sign up to set email alerts
|

A Demand Analysis for Crustaceans at the U.S. Retail Store Level

Abstract: & This study used a LA=AIDS model to estimate demand system for crustacean species, shrimp, crab, crawfish and lobster at the U.S. retail store level. Shrimp demand is price elastic; crab, crawfish and lobster are price inelastic. Shrimp price significantly affects market shares of crustacean products. Shrimp has more substitutes than other crustaceans, and lobster has less substitutes than others. The demand for crab and lobster grow faster than the demand for shrimp and crawfish when expenditure increases. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Moreover, the COVID‐19 pandemic and ensuing restaurant shutdowns further highlighted the importance of understanding retail seafood sales before the onset of the pandemic and the subsequent changes. Previous scanner data studies have focused on selected species or a single disaggregated product form (Dey et al, 2014, 2017; Nguyen et al, 2013; Singh et al, 2012, 2014). Moreover, those scanner datasets are now more than a decade old.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the COVID‐19 pandemic and ensuing restaurant shutdowns further highlighted the importance of understanding retail seafood sales before the onset of the pandemic and the subsequent changes. Previous scanner data studies have focused on selected species or a single disaggregated product form (Dey et al, 2014, 2017; Nguyen et al, 2013; Singh et al, 2012, 2014). Moreover, those scanner datasets are now more than a decade old.…”
Section: Discussionmentioning
confidence: 99%
“…Capps Jr. and Lambregts (1991) reported results from one of the early studies, followed by Wessells and Wallström (1999). More comprehensive studies have used scanner data to examine substitutions between United States and imported fish and seafood products (Chidmi et al, 2012), identify the determinants of retail price and sales volumes of US catfish products (Dey et al, 2014), analyze demand for crustaceans in US retail markets (Nguyen et al, 2013), assess whether there is a price premium for eco‐labeled products in UK retail seafood markets (Roheim et al, 2011), analyze demand for frozen seafood products (Singh et al, 2012; Surathkal et al, 2017), assess seasonal and spatial variations in demand and elasticities of fish products in the United States (Singh et al, 2014), and describe market trends for seafood products in US retail markets from the period of 2005–2006 to 2009–2010 (Dey et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Projected differences for the top 10 species by landed value globally taken between outcomes of meeting Paris Agreement targets (+1.5°C) and maintaining high emissions (+3.5°C). References (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…To study the impact of price and promotions (i.e., price discounts, featuring and display) on the demand for fish and seafood products, [ 39 ] used the Almost Ideal Demand System (AIDS) and reported that promotional impact is heterogeneous between categories, having both positive and negative effects. On the same topic, [ 40 ] reported a positive response to promotion for all types of seafood products and a heterogeneous cross-promotion effect that fluctuated from positive to negative, depending on the seafood category. More recently, [ 41 ] estimated an Exact Affine Stone Index (EASI) demand system to study the effect of promotions on different types of beverages and the banning of promotions of soft drinks in Scotland.…”
Section: Introductionmentioning
confidence: 99%